Ferric citrate: a novel phosphate-binding agent. Issue 1 (January 2013) - Umanath, Kausik; Niecestro, Robert; Lewis, Julia B; Dwyer, Jamie P
Ferric citrate (KRX-0502; Keryx Biopharmaceuticals, Inc., NY, USA) is a novel phosphate-binding agent presently in Phase III clinical development. Ferric citrate dissociates in the bowel lumen releasing the ferric ion to precipitate with dietary phosphorus, which is then excreted in the stool. Studies to date have shown the agent to be efficacious and safe with only mild gastrointestinal side effects. Absorption of either component of the agent (ferric iron or citrate) has the potential to be of benefit for patients with end-stage renal disease. An ongoing Phase III trial is confirming the safety and efficacy of ferric citrate as a phosphate binder in dialysis patients.